Prediction model and consequence analysis for riverine oil spills - Yang, Yu-feng; Wang, Shu; Zhu, Zhen-duo; Jin, Long-zhe (Frontiers in Environmental Science, 2022)
Long-distance oil and gas pipelines play an important role in ensuring energy imports, but can cause riverine oil spills and threaten public health and the environment. The emergency disposal of spilled oil is affected by a number of factors such as the difficulty of disposal and the long recovery cycle; however, there are deficiencies in the understanding of river oil spills. In this study, a prediction model of the river oil spill trajectory based on the random walk particle tracking algorithm was constructed. The performance of the model was tested by simulating the Enbridge Line 6B Oil Discharge scenario occurred in the United States in 2010. The temporal and spatial variations of the oil pollution zone in downstream and vertical directions were studied, and the interception effects on the arrival time of oil in key sections were obtained. Results showed that after the spilled oil entered the surface water body, the tiny oil droplets generated by crushing can remain underwater for a long time, making them difficult to detect and intercept. It can further combine with suspended particles in the water, settle, and pollute the riverbed, which has a greater potential for harm and risk. The model offers helpful information for the first-phase emergency response for riverine oil spills.